Advances in gecko-inspired climbing robots: from biology to robotics—a review - Xiang, Wenrui; Honarvar Shakibaei Asli, Barmak (MDPI, 2025)
Wall-climbing robots have garnered significant attention for their ability to operate in hazardous environments. Among these, bioinspired gecko robots exhibit exceptional adaptability and climbing performance due to their flexible morphology and intelligent motion strategies. This review systematically analyzes studies published between 2000–2025, sourced from IEEE Xplore, Web of Science, and Scopus databases, to explore the biological principles of gecko adhesion and locomotion. A structured literature review methodology is employed, through which representative climbing robots are systematically categorized based on spine flexibility (rigid vs. flexible) and attachment mechanisms (adhesive, suction, claw-based). We analyze various motion control strategies, from hierarchical architectures to advanced neural algorithms, with a focus on central pattern generator (CPG)-based systems. By synthesizing current research and technological advancements, this paper provides a roadmap for developing more efficient, adaptive, and intelligent wall-climbing robots, addressing key challenges and future directions in the field.
Keywords: gecko-inspired robots; motion control strategies; bioinspired robotics; adhesion mechanisms; CPG-based control; 40 Engineering; 4009 Electronics, Sensors and Digital Hardware